Synthesis, characterization, spectral and electrical properties of peripherally tetratriazole-substituted phthalocyanines and its metal complexes - DUMLUDAĞ, FATİH (ELSEVIER SCIENCE SA, 2012)
The substituted [1,2,4]triazole 3 was obtained from the reaction between compound 1 and compound 2. Novel substituted phthalonitrile 5 was prepared by the substitution of the nitro group of 4-nitrophthalonitrile 4 with triazole moiety 3. The synthesis of metal-free, zinc, nickel, cobalt and copper phthalocyanines with four substituted [1,2,4]triazole groups on peripheral position were performed from cyclotetramerization of novel substituted dinitrile compound 5. Metal-free phthalocyanine 6 and its Zn-, Ni-, Co- and Cu- complexes 7-10 were prepared in DMAE at reflux temperature. All new compounds were characterized by a combination of elemental analyses, IR, H-1/C-13 NMR, MS and UV-vis spectroscopy. Aggregation behaviors of NiPc 8 and CuPc 10 were also investigated. While NiPc 8 was aggregated in acetone, DMF, DMSO, THF, ethylacetate and toluene and non-aggregated in dichloromethane and pyridine at 10 x 10(-6) mol dm(-3) concentration, CuPc 10 showed monomeric behavior in dichloromethane, DMSO, DMF, pyridine, THF and showed aggregation in acetone, ethylacetate and toluene at 14 x 10(-6) mol dm(-3) concentration. On the other hand, substituted NiPc 8 and CuPc 10 did not show aggregation behavior between 4 x 10(-6)-14 x 10(-6) mol dm(-3) concentration range in chloroform. Dc and ac conductivity and Impedance Spectroscopy (IS) studies were also done on thin films of compounds 6, 7, 8, 9 and 10 as a function of temperature (295-523 K) and frequency (40-10(5) Hz) under vacuum (similar to 2 x 10(-3) mbar) in dark. The compounds 7, 8, 9 and 10 showed nearly same dc conductivity values in the measured temperature range. Variation of dc conductivity of 6, 7, 8, 9 and 10 with temperature exhibited the semiconducting behavior. Variation of ac conductivity of the films with frequency represented by the function sigma(ac) = A omega(s). The results indicated that charge transport mechanism of the films can be explained by hopping and small polaron tunneling model for 6, 7, 8, 9 and 10 depending on temperature and frequency region. Results of the impedance spectra measurements showed that, at high temperatures, depressed semicircles with different radius indicate deviation from Debye dispersion relation. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Phthalocyanine; Aggregation; Electrical characterization; Impedance spectra; Semiconductor; Conductivity; GAS-SENSING PROPERTIES; DECKER LU(III) PHTHALOCYANINES; MICROWAVE-ASSISTED SYNTHESIS; SCHIFF-BASE; STRUCTURAL-CHARACTERIZATION; ELECTROCHEMICAL PROPERTIES; THIN-FILMS; CONDUCTIVITY; FREQUENCY; METALLOPHTHALOCYANINES